THE ITALIAN WATER INLAND TRANSPORT SCENARIO AND MAJOR INLAND PORTS (Perner's Contacts, 2018)
The purpose of this article is to introduce the main Italian inland ports and the principal Italian rivers in the context of the Italian water inland transport. The work, for its big part, is focused on the major Italian idroviary system (Padano-Veneto), showing the most relevant features (connections, canals and related ports).
Keywords: inland water transport, inland ports, inland waterways